2023
DOI: 10.21511/ppm.21(4).2023.18
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of employee digital transformation readiness and job performance: A case of SMEs in Vietnam

Nguyen Thi Thu Thuy,
Hong Pham Thi Thanh,
Tran Thi Bich Ngoc
et al.

Abstract: The subject of stimulating employees toward digital transformation has always been one of the most significant topics, attracting the interests of scientists and decision-makers. This study analyzes the impact of critical factors, including self-efficacy, attitude, leadership, and employee characteristics on employee readiness for digital transformation and job performance. The variables were selected based on the extended theory of planned behavior and personal resource adaption models. To achieve the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The introduction of new technology necessitated training for microfinancing personnel, aligning with findings in studies on e-resource readiness, and emphasizing the need for training in computer applications and data management (Abdulkareem, 2021;Shah et al, 2023). A study on the determinants of employee digital transformation readiness and job performance revealed that employees' attitude, self-efficacy, and characteristics affected their readiness for digital transformation (Thu et al, 2023). From the point of view of customers, a study on customer preference shift showed that customers change their preferences once they observe obvious improvements in previous practices (Narsico & Narsico, 2023).…”
Section: Customer Data Managementmentioning
confidence: 85%
“…The introduction of new technology necessitated training for microfinancing personnel, aligning with findings in studies on e-resource readiness, and emphasizing the need for training in computer applications and data management (Abdulkareem, 2021;Shah et al, 2023). A study on the determinants of employee digital transformation readiness and job performance revealed that employees' attitude, self-efficacy, and characteristics affected their readiness for digital transformation (Thu et al, 2023). From the point of view of customers, a study on customer preference shift showed that customers change their preferences once they observe obvious improvements in previous practices (Narsico & Narsico, 2023).…”
Section: Customer Data Managementmentioning
confidence: 85%